2021
DOI: 10.3389/fpls.2021.684784
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Short-Term Exposure to Low Temperatures During the Booting Stage on Starch Synthesis and Yields in Wheat Grain

Abstract: Low temperatures (LT) in spring can have a major impact on the yields of wheat in winter. Wheat varieties with different cold sensitivities (the cold-tolerant Yannong 19 variety and the cold-sensitive Yangmai 18 variety) were used to study the responses of the wheat grain starch synthesis and dry material accumulation to short-term LT during the booting stage. The effects of short-term LT on the activities of key wheat grain starch synthesis enzymes, starch content and grain dry-matter accumulation were determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 72 publications
2
14
0
Order By: Relevance
“…Low temperature (LT) is an important abiotic stress that seriously affects the production and development of global cereal crops (Huang et al, 2021;Zhang et al, 2021). Several studies have found that the post-silking/grain filling stage is very sensitive to LT during the growth cycle of cereal crops (Thakur et al, 2010;Luo, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Low temperature (LT) is an important abiotic stress that seriously affects the production and development of global cereal crops (Huang et al, 2021;Zhang et al, 2021). Several studies have found that the post-silking/grain filling stage is very sensitive to LT during the growth cycle of cereal crops (Thakur et al, 2010;Luo, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Low-temperature stress during spring depicts that the temperature in the season of rebirth, growth, and development rises rapidly, and during late spring season, the temperature is generally lower than optimum. Following this, when the crop development enters the anther differentiation phase, the resistance to frost will descend sharply (Zhang et al, 2015(Zhang et al, , 2019(Zhang et al, , 2021. This will subject toward fruitlessness or adverse production losses sometimes 30-50% once the crop plant encounters low-temperature stress (Zheng et al, 2016;Liu et al, 2019).…”
Section: Global Climate Change and Impacts On Food Securitymentioning
confidence: 99%
“…Variations in ambient temperature during the grain-filling stage affect starch accumulation (Ahmed et al, 2008;Zhang et al, 2021) and the amylose-amylopectin contents of the rice endosperm (Jiang et al, 2003;Zhen-Zhen et al, 2015). Prevailing low-temperature stress during the grain-filling stage will prolong the grain-filling period from 32 days to >50 days (Ahmed et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The product of filling efficiency and sink capacity collectively produce the grain yield in cereals (Kato et al, 2007;Zhang et al, 2021). Wider breeding efforts globally have increased the grain sink capacity and maximized the size of sink organs likely to be harvested to further increase the grain yield primarily by enhancing the spikelet number on each panicle (Kato et al, 2007;Zhang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation